2004
DOI: 10.1017/s0031182004005839
|View full text |Cite
|
Sign up to set email alerts
|

Stability ofCorynosomapopulations with fluctuating population densities of the seal definitive host

Abstract: In theory there should be a strong coupling between host and parasite population sizes. Here, we investigated population size and structure in 3 species of acanthocephalans, Corynosoma semerme, C. strumosum and C. magdaleni, in ringed seals (Phoca hispida) from the Bothnian Bay over a period of more than 20 years. During this period, seal numbers first decreased markedly and then increased steadily ; at the same time, a paratenic fish host particularly important for C. strumosum has gradually disappeared from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 15 publications
(26 reference statements)
0
26
0
Order By: Relevance
“…Fish species composition was considered stable over the time period studied (see e.g. Lehtonen et al 1993;Valtonen et al 2004), and food web studies normally integrate data over extended periods. Amundsen et al (2009) assembled information for the Takvatn pelagic web over 21 years.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fish species composition was considered stable over the time period studied (see e.g. Lehtonen et al 1993;Valtonen et al 2004), and food web studies normally integrate data over extended periods. Amundsen et al (2009) assembled information for the Takvatn pelagic web over 21 years.…”
Section: Methodsmentioning
confidence: 99%
“…Amundsen et al (2009) assembled information for the Takvatn pelagic web over 21 years. Parasites and diets of 109 ringed (Phoca hispida) and 49 grey seals (Halichoerus grypus) were obtained from the senior author's data on alimentary tract contents) from 1977 to 1999 (see Valtonen et al 2004), information on seals' diets being supplemented from the literature for the Baltic Sea (Söderberg 1975;Tormosov and Rezvov 1978;Stenman and Pöyhönen 2005). Diets of bird species were inferred from the literature (Feltham 1990;Fox et al 1990;Kubetzki and Garthe 2003;Gilliland et al 2004;Ross et al 2005;Santoul 2005) and an on-line database (http://bna.birds.cornell.edu/bna).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gulf of Bothnia Chubb et al 1995, Valtonen et al 2004, Bergman 2007 How the indicator describes the Baltic marine environment?…”
Section: Alimentary Track Intestinementioning
confidence: 99%
“…However, parasite abundance appeared unrelated to the density of amphipods in the sample, so it is not obvious that there is a tight coupling between amphipod and acanthocephalan populations. Similarly, Valtonen et al (2004) found that the abundance of three seal acanthocephalans in the Bothnian Bay varied little in response to sizeable fluctuations in the intermediate and definitive host populations.…”
Section: Fuli Et Al 2008) Whereas Pomphorhynchus Laevis Zoega Inmentioning
confidence: 87%